A Study of the Romer and Romer Monetary Policy Shocks Using Revised Data - Fredrik N. G. Andersson; Josefin Kilman (Lund University, School of Economics and Management, Department of Economics, 2021)
Romer and Romer (2004) propose a simple method to estimate monetary policy shocks using forecasts and real-time data. However, such data is not always (publicly) available, especially in a historical context. We explore the consequences of using revised data instead of the original forecast and real-time data when estimating policy shocks using the Romer and Romer framework. To this end, we estimate policy shocks for the same period as Romer and Romer. We find that using revised data has little impact on actual shock estimates, and the estimated effects of monetary policy shocks are similar.
Keywords: E20; E30; E40; E50; E60; 330; Monetary policy shocks; prices; GDP